Caffeoyl-CoA 3-O-methyltransferase gene family in jute: Genome-wide identification, evolutionary progression and transcript profiling under different quandaries - Akhter, Saima; Sami, Asif Ahmed; Toma, Tamanna Islam; Jahan, Bushrat; Islam, Tahmina (Frontiers in Plant Science, 2022)
Jute (Corchorus sp.), is a versatile, naturally occurring, biodegradable material that holds the promising possibility of diminishing the extensive use of plastic bags. One of the major components of the cell wall, lignin plays both positive and negative roles in fiber fineness and quality. Although it gives mechanical strength to plants, an excess amount of it is responsible for the diminution of fiber quality. Among various gene families involved in the lignin biosynthesis, Caffeoyl-CoA 3-O-methyltransferase (CCoAOMT) is the most significant and has remained mostly unexplored. In this study, an extensive in-silico characterization of the CCoAOMT gene family was carried out in two jute species (C. capsularis L. and C. olitoroius L.) by analyzing their structural, functional, molecular and evolutionary characteristics. A total of 6 CCoAOMT gene members were identified in each of the two species using published reference genomes. These two jute species showed high syntenic conservation and the identified CCoAOMT genes formed four clusters in the phylogenetic tree. Histochemical assay of lignin in both jute species could shed light on the deposition pattern in stems and how it changes in response to abiotic stresses. Furthermore, expression profiling using qPCR showed considerable alteration of CCoAOMT transcripts under various abiotic stresses and hormonal treatment. This study will lay a base for further analysis and exploration of target candidates for overexpression of gene silencing using modern biotechnological techniques to enhance the quality of this economically important fiber crop.